2020
DOI: 10.1111/ane.13342
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian syndrome in Nigerian women with epilepsy on carbamazepine/levetiracetam monotherapy

Abstract: The study is aimed at comparing effects of older drugs like carbamazepine (CBZ) and newer agent like levetiracetam (LEV) on polycystic ovarian syndrome (PCOS) in women with epilepsy (WWE). Methods: An interviewer-based questionnaire was used to obtain relevant clinical information from 50 WWE on CBZ and LEV monotherapy, respectively, and 50 age-matched controls. The diagnosis of epilepsy was clinical with electroencephalographic features taken into consideration and the seizures classified using the 2017 Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The study by Svalheim et al 37 demonstrated no significant effect of LEV on hormones in WWE. However, a recent study by Ogunjimi et al 14 showed that the proportion of PCOS in WWE with LEV monotherapy was significantly higher than that in those with CBZ monotherapy and healthy controls (44%, 16%, and 4%, respectively), which supports the findings of the present study. The rates of hyperandrogenism, hirsutism, and plasma T concentrations in patients undergoing LEV monotherapy were significantly higher than those in healthy controls and patients undergoing CBZ monotherapy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study by Svalheim et al 37 demonstrated no significant effect of LEV on hormones in WWE. However, a recent study by Ogunjimi et al 14 showed that the proportion of PCOS in WWE with LEV monotherapy was significantly higher than that in those with CBZ monotherapy and healthy controls (44%, 16%, and 4%, respectively), which supports the findings of the present study. The rates of hyperandrogenism, hirsutism, and plasma T concentrations in patients undergoing LEV monotherapy were significantly higher than those in healthy controls and patients undergoing CBZ monotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of PCOS was significantly higher in WWE who had taken LEV for at least 1 year than in those who had taken the same for less than 1 year or never (22.97% vs. 12.64%, p = .0409). Since LEV is a relatively novel medication for epilepsy, only a few studies have been conducted on its effect on PCOS and reproductive endocrinology 14,37–39 . The study by Svalheim et al 37 demonstrated no significant effect of LEV on hormones in WWE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASMs may be safer than traditional drugs, and their reproductive endocrine effects have not been extensively studied. In addition, the effects of epilepsy and anti-epileptic drugs on reproductive endocrine function vary with factors such as the type of epilepsy, the age at onset of seizures, the age when treatment was initiated, and the types TABLE 1 | The influence of anti-seizure medications (ASMs) on the hypothalamic-pituitary-ovarian (HPO) axis (5,14,16,72,134,140,142,143).…”
Section: Discussionmentioning
confidence: 99%
“…Its reduction contributes to the development of IR (93) (Figure 3). the proportions are 44%, 20%, and 24% respectively (134). LEV may also affect the HPG axis of female rats (135).…”
Section: The Possible Mechanism Of Ir/ Hyperinsulinemia Caused By Vpamentioning
confidence: 93%